2014
DOI: 10.1088/0004-637x/781/1/32
|View full text |Cite
|
Sign up to set email alerts
|

On a Solar Origin for the Cosmogenic Nuclide Event of 775 A.D.

Abstract: We explore requirements for a solar particle event (SPE) and flare capable of producing the cosmogenic nuclide event of 775 a.d., and review solar circumstances at that time. A solar source for 775 would require a >1 GV spectrum ∼45 times stronger than that of the intense high-energy SPE of 1956 February 23. This implies a >30 MeV proton fluence (F 30 ) of ∼8 × 10 10 proton cm −2 , ∼10 times larger than that of the strongest 3 month interval of SPE activity in the modern era. This inferred F 30 value for the 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 31 publications
0
92
1
Order By: Relevance
“…This event is confirmed by annual 14 C data from a German oak tree , Russian and American tree samples (Jull et al 2014), New Zealand trees (Güttler et al 2013), etc., and corals from the Chinese Sea (Liu et al 2014) According to model simulations, the production of 14 C appears in agreement with that of 10 Be Melott and Thomas 2012;Pavlov et al 2013). Although some exotic scenarios were proposed for the event: an unidentified nearby supernova ); a gamma-ray burst (Hambaryan and Neuhäuser 2013;Pavlov et al 2013); or even a cometary impact on Earth (Liu et al 2014), it is generally accepted now that it was a signature of a (probably, consequence of) extreme SEP event Eichler and Mordecai 2012;Usoskin et al 2013;Melott and Thomas 2012;Thomas et al 2013;Cliver et al 2014). A detailed analysis performed by Mekhaldi et al (2015) not only confirmed its solar origin but also made it possible to assess, based on data from different cosmogenic isotopes, the reconstructed integral spectrum as shown in Fig.…”
Section: The Event Of 775 Ad: the Worst Case Scenario?mentioning
confidence: 82%
“…This event is confirmed by annual 14 C data from a German oak tree , Russian and American tree samples (Jull et al 2014), New Zealand trees (Güttler et al 2013), etc., and corals from the Chinese Sea (Liu et al 2014) According to model simulations, the production of 14 C appears in agreement with that of 10 Be Melott and Thomas 2012;Pavlov et al 2013). Although some exotic scenarios were proposed for the event: an unidentified nearby supernova ); a gamma-ray burst (Hambaryan and Neuhäuser 2013;Pavlov et al 2013); or even a cometary impact on Earth (Liu et al 2014), it is generally accepted now that it was a signature of a (probably, consequence of) extreme SEP event Eichler and Mordecai 2012;Usoskin et al 2013;Melott and Thomas 2012;Thomas et al 2013;Cliver et al 2014). A detailed analysis performed by Mekhaldi et al (2015) not only confirmed its solar origin but also made it possible to assess, based on data from different cosmogenic isotopes, the reconstructed integral spectrum as shown in Fig.…”
Section: The Event Of 775 Ad: the Worst Case Scenario?mentioning
confidence: 82%
“…These values serve as observational upper limits on the strength of SPEs on the timescale of tens of millennia, they are consistent with our estimates of physical limits presented in Table 2 if we assume that the fluence resulted in the production of the cosmogenic isotopes was accumulated during several single events occurred within three months. The considerations of Cliver et al [11] challenge a suggestion that the 775 event is likely of solar origin. This event could originate from high-energy irradiation of the atmosphere by a Galactic gamma-ray burst [13].…”
Section: Discussion: Ultimate Fluxes and Fluencesmentioning
confidence: 98%
“…We use the characteristic time of fluence accumulation obtained from the observations to derive an ultimate fluence of a single solar proton event (SPE). Our estimates are consisted with the observational upper limits on the strength of SPEs on the timescale of tens of millennia [10] and during the most active interval 1945 -1995 of the last 2000 years [11].…”
Section: Pos(icrc2015)098mentioning
confidence: 99%
“…Two events have been confirmed as the events by high-resolution annual data of cosmogenic radionuclides: the events of 775 AD and 993 AD [10,11,12,13,14]. Despite some ongoing debates about the origin of these events [15,12,16], solar origin of the spikes due to extreme SEP events is the most likely source, and the overall production of the 14 C and 10 Be nuclides can be calculated.…”
Section: Introductionmentioning
confidence: 94%